The Influence of Variations in Cotton, Denim, and Linen Fabrics on Noise Reduction: A Study on Industrial Applications - Muhamad Iqbal; Syifa Rifda Hanifah; Nurul Hidayah (Poltekkes Kemenkes Surabaya, 2025)
Noise is a form of environmental pollution that is receiving increasing attention due to its negative impact on human health and quality of life, so it is essential to understand and manage its risks. Based on the observations of the work environment in the P.T. washing room. X Cimahi, which comes from the Steamer Drying Engine, initial measurements for 10 minutes showed that the noise level in the room was above the threshold value at 89.1 dBA, so efforts were needed to reduce the noise level. This research discusses the influence of different types of barrier patchwork media on reducing noise levels. The research carried out was experimental with quantitative experimental methods and a pre-test – post-test research design to find the effect of specific treatments on other variables under controlled conditions in such a way. Sampling in this research was carried out in May 2023 for six days with a measurement time of 10 minutes during productive hours in each work shift to obtain noise level measurements 36 times. This research obtained pre-test results from each of the three treatments in the 88.5-90.5 dBA range. Meanwhile, post-test results from the three treatments obtained an average reduction percentage of 22.6% for cotton patchwork, 17.0% was obtained from denim patchwork, and 12.4% from linen patchwork. The noise level after installing the noise barrier on patchwork media with a thickness of 8 cm on a variety of cotton patchwork media materials, denim patchwork, and linen patchwork can reduce the noise level by 20.2-21.0 dBA, 15.1-15.6 dBA, and 10.9-11.4 dBA. With the significant reduction in noise levels, this patchwork noise barrier can be used as an alternative for noise control.